2014
DOI: 10.1016/j.eurpsy.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the efficacy and tolerability of Clozapine in the treatment of youth with early onset schizophrenia

Abstract: Available data although limited in terms of number of studies are consistent in demonstrating that CLZ is effective and generally safe in the treatment of refractory EOS provided patients are regularly monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 48 publications
5
92
0
3
Order By: Relevance
“…These data are supported by a review covering 16 clinical studies and four case reports (n = 798) with early onset schizophrenia that also linked relevant weight gain to treatment with clozapine with an incidence of 20 --64%. The authors found an association between increased risk and length of exposure [64]. Beduin and de Haan reviewed data on SGAs used off-lable for impulse regulation disorders and found weight gain associated with all SGAs, but more pronounced in children and patients treated with clozapine and olanzapine [65].…”
Section: Weight Gain Due To Clozapinementioning
confidence: 99%
“…These data are supported by a review covering 16 clinical studies and four case reports (n = 798) with early onset schizophrenia that also linked relevant weight gain to treatment with clozapine with an incidence of 20 --64%. The authors found an association between increased risk and length of exposure [64]. Beduin and de Haan reviewed data on SGAs used off-lable for impulse regulation disorders and found weight gain associated with all SGAs, but more pronounced in children and patients treated with clozapine and olanzapine [65].…”
Section: Weight Gain Due To Clozapinementioning
confidence: 99%
“…In fact, 17 (81 %) had tried clozapine at least once during follow-up, significantly more than in the non-ECT group (N = 8, 38.1 %). Clozapine has been reported to be the best option for treatment-resistant SSD in adolescents and seems to be more effective in the long term for this population [4,[36][37][38]. In a previous study, our group found that patients treated with ECT and clozapine had fewer rehospitalizations after 1 year follow-up than patients treated with ECT and other APs [15].…”
Section: Discussionmentioning
confidence: 80%
“…However, the anticholinergic/adrenergic effects of these medications may combine to aggravate unwanted side effects of clozapine such as constipation, impaired visual acuity, and urinary retention. Another option is the use of ophthalmologic drops with anticholinergic properties, such as atropine, as a mouthwash, before going to sleep (Schneider et al, 2013). There are also recent findings on the use of atropine drops three times a day for a week, combined with hyoscine (antimuscarinic agent).…”
Section: Hypersalivation (Sialorrhea/drooling)mentioning
confidence: 98%
“…The total dosage administration may be rearranged over the day so that a lower dose is administered at nighttime (Barnes et al, 2012). Another option is restricting fluids before bedtime and avoiding consumption of caffeine, alcohol, and other drinks with diuretic or bladder irritant properties (Barnes et al, 2012;Schneider et al, 2013). Double voiding before bedtime is another option (Schneider et al, 2013).…”
Section: Nocturnal Enuresismentioning
confidence: 99%
See 1 more Smart Citation